Human oral bioavailability and pharmacokinetics of tocotrienols from tocotrienol-rich (tocopherol-low) barley oil and palm oil formulations - Astrid M. Drotleff; Christoph Bohnsack; Inga Schneider; Andreas Hahn; Waldemar Ternes (Journal of Functional Foods, 2014)
Tocotrienols are members of the vitamin E family thought to have hypocholesterolaemic, anti-cancer, and neuroprotective properties. We compared the bioavailability and pharmacokinetics of a single oral dose of 450 mg total tocotrienols from α-tocotrienol-rich barley oil and γ-tocotrienol-rich palm oil (both also low in tocopherols) in seven healthy male human subjects 0–24 h post-dose. The maximum α-tocotrienol plasma concentration (22.57 ± 2.84 mg/L, 2.1 ± 0.3 h) was significantly (p < 0.001) higher for barley oil than for palm oil (5.25 ± 0.99 mg/L, 2.3 ± 0.6 h). The area under the curve (0–24 h) of total (α-, β-, γ-, δ-) tocotrienols was significantly (p < 0.001) (2.6fold) higher in the barley oil group, where the total (0–24 h) urinary metabolites carboxyethyl-hydroxychromans (CEHC) and carboxymethylbutyl-hydroxychromans (CMBHC) were also significantly (p < 0.05) (1.2fold) higher (163.9 ± 19.2 μmol). Thus, due to its high proportion of α-tocotrienol, which is known for its preferential absorption, the barley oil formulation was superior to the commercial palm oil formulation. This provides support for the application of tocotrienols from barley oil in the functional foods field.